2015
DOI: 10.1038/tp.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with n-3 fatty acids from weaning limits brain biochemistry and behavioural changes elicited by prenatal exposure to maternal inflammation in the mouse model

Abstract: Prenatal exposure to maternal immune activation (MIA) increases the risk of schizophrenia and autism in the offspring. The MIA rodent model provides a valuable tool to directly test the postnatal consequences of exposure to an early inflammatory insult; and examine novel preventative strategies. Here we tested the hypotheses that behavioural differences in the MIA mouse model are accompanied by in vivo and ex vivo alterations in brain biochemistry; and that these can be prevented by a post-weaning diet enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 92 publications
(101 reference statements)
4
40
0
1
Order By: Relevance
“…47 Another study showed that prenatal exposure to maternal inflammation influences the levels of N-acetylaspartate/creatine and myo-inositol/creatinine in the cingulate cortex of mice. 48 In fact, abnormal white matter microstructure in the left anterior cingulate cortex has been found in mice exposed to an immune challenge in early or late prenatal development, 49 which is consistent with our findings in the current study. Using data from the PGC-I, we found that the blue and brown modules harboured the genes predominantly related to the histone methyltransferase activity and the histone-lysine N-methyltransferase activity.…”
Section: Discussionsupporting
confidence: 91%
“…47 Another study showed that prenatal exposure to maternal inflammation influences the levels of N-acetylaspartate/creatine and myo-inositol/creatinine in the cingulate cortex of mice. 48 In fact, abnormal white matter microstructure in the left anterior cingulate cortex has been found in mice exposed to an immune challenge in early or late prenatal development, 49 which is consistent with our findings in the current study. Using data from the PGC-I, we found that the blue and brown modules harboured the genes predominantly related to the histone methyltransferase activity and the histone-lysine N-methyltransferase activity.…”
Section: Discussionsupporting
confidence: 91%
“…Given that the vast majority of children of mothers who experience an infection do not develop psychiatric disease, recent consideration has been given to maternal and foetal mechanisms of resilience to perinatal infection and inflammation: these include maternal nutritional status, the microbiome, and a variety of postnatal environmental factors (235). In terms of interventions within the MIA paradigm that have potential widespread relevance, dietary supplementation with omega-3 polyunsaturated fatty acids (PUFAs) may represent an attractive preventative strategy (236,237).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, minocycline, a microglia (a type of macrophage-like cell in the brain) modulator, prevents the emergence of MIA-induced behaviors and changes in cytokines in the adult brain when given during exposure to peripubertal stress (3, 4, 75). Several SZ and ASD-related phenotypes in MIA offspring can also be prevented with probiotic treatment(72), anti-cytokine antibody treatment(19, 76), and environmental enrichment (77) or maternal dietary supplementation with zinc(78, 79), n-3 polyunsaturated fatty acids (80, 81) or N-acetyl-cysteine (NAC)(82). Finally, one of the most exciting potential treatments is anti-purinergic therapy, which completely reverses several ASD-related phenotypes in MIA offspring(4).…”
Section: Implications For Treatment Of Psychiatric Disordersmentioning
confidence: 99%